Design And Development Of An Augmented Reality Module For Learning Arabic Collocations - Md Noor, Mohammad Lukman Al Hakim; Md. Ghalib, Mohd Feham; Abdul Hamid, Mohd Fauzi; Abdul Gani, Muhamad Zamri; Aziz, Nurul Izzatie; Sahrir, Muhammad Sabri; Yusoff, Mohamad Akashah; Isa, Muhamad Aiman (Ijaz Arabi Journal of Arabic Learning, 2025)
This study investigates an instructional module's design, development, and effectiveness for learning Arabic collocations using Augmented Reality (AR) technology. A needs analysis was conducted to identify students’ challenges with Arabic collocations and their preferred learning strategies. Based on these insights, the module was designed using the ADDIE Model, integrating multimedia elements such as text, images, audio, animations, video, and 2D/3D models to improve engagement and comprehension. The AR-based module, AR Collocation, was implemented among 30 advanced learners at the International Islamic University Malaysia (IIUM). Data were collected through interviews, questionnaires, and student feedback, focusing on usability and learning outcomes. The results showed that the AR module significantly enhanced students’ understanding of Arabic collocations, with a mean score of 4.3 (p 0.05). Students also rated the readability of fonts and the multimedia components highly (mean values: 4.73 and 4.87), expressing overall satisfaction with the interactive features. This study concludes that AR-based instructional modules can improve Arabic language learning and recommends further exploring AR's potential in teaching Arabic as a second language.